2021
DOI: 10.1161/strokeaha.120.031454
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Atrial Fibrillation and Long-Term Risk of Stroke in Patients Undergoing Liver Transplantation

Abstract: Background and Purpose: Postoperative atrial fibrillation (POAF) is the commonest cardiovascular complication following liver transplantation (LT). This study sought to assess a possible association of POAF with subsequent thromboembolic events in patients undergoing LT. Methods: A retrospective cohort study of consecutive adults undergoing LT between 2010 and 2018 was undertaken. Patients were classified as POAF if atrial fibrillation (AF) was document… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…17 , 18 Degeneration of the atrial myocardium with aging may lead to a loss of side-to-side electrical coupling between muscle fibers, slowing down electrical conduction of the sinoatrial and atrioventricular nodes and atria, thereby providing an anatomic or electrophysiologic substrate for arrhythmogenesis. 19 Left atrial (LA) enlargement is a manifestation of potentially fibrosis and adverse atrial remodeling, 20 in addition to age, it can also be exacerbated by atrial ischemia in the presence of stenosis of coronary artery supplying to the atria. 21 On the basis of varying degrees of changes in the atria, inflammation and activation of the autonomic nervous system are the principal transient factors associated with CABG that trigger POAF.…”
Section: Discussionmentioning
confidence: 99%
“…17 , 18 Degeneration of the atrial myocardium with aging may lead to a loss of side-to-side electrical coupling between muscle fibers, slowing down electrical conduction of the sinoatrial and atrioventricular nodes and atria, thereby providing an anatomic or electrophysiologic substrate for arrhythmogenesis. 19 Left atrial (LA) enlargement is a manifestation of potentially fibrosis and adverse atrial remodeling, 20 in addition to age, it can also be exacerbated by atrial ischemia in the presence of stenosis of coronary artery supplying to the atria. 21 On the basis of varying degrees of changes in the atria, inflammation and activation of the autonomic nervous system are the principal transient factors associated with CABG that trigger POAF.…”
Section: Discussionmentioning
confidence: 99%
“… 12 14 Postoperative AF was also associated with an 8-fold increased risk of stroke and systemic embolism events over a median follow-up of 4.9 years. 15 …”
Section: Discussionmentioning
confidence: 99%
“…Anticoagulant therapy was not considered in the present case, due to the following factors: First, the consideration of postoperative bleeding risk; Secondly, the CHA 2 DS 2 VASc score of the patient was 0. CHA 2 DS 2 VASc score has been well validated in assessing the risk of thromboembolism associated with AF, 9 and may also estimate the risk of stroke in patients with AF, with higher scores indicating a greater risk of stroke, 15 so the risk of a thromboembolic event was considered to be low in the present case; and Thirdly, a previously published study showed that early anticoagulant therapy did not improve clinical outcomes in critically ill patients with new onset AF, 30 and a systematic review didn’t support early anticoagulant therapy for new onset AF whilst patients are critically ill. 31 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both pre‐existing AF and new‐onset post‐operative AF after liver transplantation have been associated with adverse outcomes. The incidence of new‐onset AF in the post‐operative period was reported between 6.8% and 10.2% 8,66–68 . In a retrospective registry of 1387 patients who underwent liver transplantation, post‐operative AF, defined as new‐onset AF within 30 days of liver transplant, occurred in 7.4% of patients 66 .…”
Section: Atrial Fibrillation In Cirrhosismentioning
confidence: 99%